Youth‐led peer support program meets needs of MH system. Issue 19 (8th May 2020) - Canady, Valerie A.
Abstract : Helping young people understand their mental health needs and to ultimately take charge of them is only part of the story involving an innovative Washington state–based youth‐led peer support program. The youth and young adults who graduate to become certified peer counselors go on to work in community mental health centers or seek higher education, with the goal of becoming therapists, social workers or psychiatrists.